PENGATURAN TERHADAP PELAKU PROSTITUSI MENGGUNAKANAPLIKASI MICHAT DALAM HUKUM PIDANA INDONESIA - Farhan Hevin Pratama; Davit Rahmadan; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Online prostitution is a practice of prostitution that uses internet social media as a means ofcommunication or a liaison between commercial sex workers (PKS), pimps and their users. Socialmedia that is often used by commercial sex workers and pimps recently is MiChat social media.MiChat is a private messaging application as well as group messaging, sharing photos,videos and voice messages. MiChat has an excellent feature, namely People Nearby where userscan find new friends based on the closest location. This feature is often misused by commercial sexworkers (PSK), and pimps in carrying out the criminal act of online prostitution. In a sense, thisapplication can connect a person with people whose location is nearby, that is, within a certainradius, by presenting a profile photo and location distance, so that service users are not difficult tofind prostitution service providers that suit their tastes. The offer of commercial sex services bycommercial sex workers is carried out via chat on the MiChat application.Not only that, online prostitution activities in the MiChat application will further develop ifthe parties involved in the practice of misusing the MiChat application as a means of onlineprostitution crime are not given appropriate punishments according to the actions they havecommitted, then they will continue to repeat them and always feel safe. from legal bondage.Therefore, a firm legal policy is needed in handling online prostitution cases in the MiChatapplication for parties involved in this practice, with the aim of obtaining an effective solution inhandling these cases.This research will examine the main issues according to the scope and identification ofproblems through a normative juridical approach. Based on normative research methods, the datasources used in this research are secondary data sources which consist of 3 legal materials,namely: primary legal materials, secondary legal materials, and tertiary legal materials. Datacollected from literature studies.Keywords: Regulation - Prostitutes - Michat Application - Indonesian CriminalLaw